Membangun Minat dan Kemampuan Mahasiswa Menulis Industri Kreatif Berbasis Lokal Melalui Pembelajaran Jurnalistik Sastra - Eddy Pahar Harahap (Proceeding International Conference on Malay Identity, 2022)
Abstract: In the last ten years, the government has realized a local-based creative industry program as one of the nation's peculiarities. This is based on Presidential Instruction No. 6/2006, which states that one of the sources of enrichment for local-based creative industries is local cultural wisdom. In the development of the creative industry is increasingly known, it is necessary to have writing skills from students as novice writers. Research subjects are fifth semester students who take Feature courses. Research data in the form of students' writing skills; title, intro, dialogue, story atmosphere, plot, theme, characterization, setting, and moral message closing the feature of local-based creative industry wisdom. The results of the overall study of students' ability to write local-based creative industries concluded that the range of abilities was 'good'. Based on the conclusions, the suggestions put forward; (1) features are very easy to write by students as novice writers, so students are motivated to write local-based creative industries, and (2) feature data is sourced from the results of field research through; observation, interview, investigation, and reportage. Collecting data like this is fun for students, as young researchers. Based on these two things, the suggestions put forward for learning literary journalism are very well developed in learning to write. Keywords: Writing, Industry, Local creative, Journalistic, literary